ANALISIS SISTEM INFORMASI AKUNTANSI PEMBAYARAN BIAYA TAGIHAN AIR PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN SIKKA (STUDI KASUS PERUSAHAAN DAERAH AIR MINUM (PDAM) CABANG TALIBURA) - Gondeliva, Maria; Dince, Maria Nona; Aurelia, Pipiet Niken (Jurnal Projemen UNIPA, 2025)
This research aims to analyze the implementation of the accounting informationa system for water bill pyments at the Talibura Branch of the Regional Drinking Water Company (PDAM) in Sikka Regency, The research employs a qualitatife approach, utilizing literature review and observation methods. The findings indicate that the use of computerized system, such as SISKA, significantly enhances the speed of recording, reporting. And improving customer service. However, challenges related to system integration. User competence, and network disruptions need to be addressed to maximize the systems’s benefits. In conclusion, the implementation of the accounting information systems has had a positive impact on the financial management of the Talibura Branch of PDAM, but efforts are needed to further improve the systems optimal performance.